2013
DOI: 10.2478/pjct-2013-0079
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of heavy metals from soil using quartz sand functionalized with organic amino silanes

Abstract: The results of the research studies concerning the binding of heavy metals (HMs) by quartz sand functionalized with amino silanes have been described. The studies have been carried out on soils sampled from the areas affected by emissions from Copper Smelter and Refinery. The research aims to increase the food safety in the areas of industrial impact. The presence of polyamine chain in the hybrid materials obtained enables a binding of heavy metals (nickel, copper, cobalt). The best results are observed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Liu et al recently reported functionalization of sand with 3‐aminopropyltriethoxysilane (APTES) and its application for uptake of hexavalent chromium . Grzesiak et al reported remediation of heavy metals from soil using quartz sand functionalized with organic amino silanes . There are also few articles on the antimicrobial sand particles prepared via surface modification, for example, with N ‐halamine acrylamidesiloxane copolymer, and cationic Moringa oleifera protein .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al recently reported functionalization of sand with 3‐aminopropyltriethoxysilane (APTES) and its application for uptake of hexavalent chromium . Grzesiak et al reported remediation of heavy metals from soil using quartz sand functionalized with organic amino silanes . There are also few articles on the antimicrobial sand particles prepared via surface modification, for example, with N ‐halamine acrylamidesiloxane copolymer, and cationic Moringa oleifera protein .…”
Section: Introductionmentioning
confidence: 99%